p53, Oxidative Stress, and Aging - Dongping Liu; Yang Xu (2010)
Mammalian aging is associated with elevated levels of oxidative damage of DNA, proteins, and lipids as a result of unbalanced prooxidant and antioxidant activities. Accumulating evidence indicates that oxidative stress is a major physiological inducer of aging. p53, the guardian of the genome that is important for cellular responses to oxidative stresses, might be a key coordinator of oxidative stress and aging. In response to low levels of oxidative stresses, p53 exhibits antioxidant activities to eliminate oxidative stress and ensure cell survival; in response to high levels of oxidative stresses, p53 exhibits pro-oxidative activities that further increase the levels of stresses, leading to cell death. p53 accomplishes these context-dependent roles by regulating the expression of a panel of genes involved in cellular responses to oxidative stresses and by modulating other pathways important for oxidative stress responses. The mechanism that switches p53 function from antioxidant to prooxidant remains unclear, but could account for the findings that increased p53 activities have been linked to both accelerated aging and increased life span in mice. Therefore, a balance of p53 antioxidant and prooxidant activities in response to oxidative stresses could be important for longevity by suppressing the accumulation of oxidative stresses and DNA damage.